Особливості раціональності у дискурсі постмодернізму - Моравецький, О. М.; Моравецкий, О. М.; Moravetskiy, O. М. (My University, 2017)
Постмодерністський «виклик» класичній раціональності полягає у спробі «перевернути» усталені смисли з метою виходу за їхні межі, що призводить до розширеного тлумачення раціональності, яка розуміється не тільки як метод пізнання дійсності, заснований на розумі, але і як структура, що має власні закони й особливості. Постмодернізм, надаючи перевагу «екстенсивності поверхні» думки перед «інтенсивністю» її «вертикалі», акцентує «ерудицію» як методологічний інструмент дослідження «множинностей», що є de facto множинністю інтерпретацій. У гносеології відбувається спроба ліквідувати картезіанську суб’єкт/об’єктну парадигму, а також – прагнення пересадити методи гуманітарних наук на ґрунт природничо-наукових дисциплін, що породжує розуміння буття та його феноменів як структур мови.

Постмодернистский «вызов» классической рациональности заключается в попытке «перевернуть» устоявшиеся смыслы с целью выхода за их пределы, что приводит к расширенному толкованию рациональности, которая понимается не только как метод познания действительности, основанный на разуме, но и как структура, имеющая собственные законы и особенности. Постмодернизм, отдавая предпочтение «экстенсивности поверхности» мысли перед «интенсивностью» ее «вертикали», акцентирует «эрудицию» как методологический инструмент исследования «множества», что является de facto множественностью интерпретаций. В гносеологии происходит попытка ликвидировать картезианскую субъект/объектную парадигму, а также – стремление пересадить методы гуманитарных наук на почву естественнонаучных дисциплин, что порождает понимание бытия и его феноменов как структур языка.

Postmodern “challenge” classic rationality is to try to “flip” a well-established meanings with the aim of going beyond their limits, leading to a broader interpretation of rationality, which is understood not only as a method of understanding reality based on reason, but also as a structure that has its own laws and peculiarities. Postmodernism, preferring the “extensiveness of the surface” thoughts before the “intensity” of its “vertical” emphasizes “knowledge” as a methodological research tool “many”, which is the de facto multiplicity of interpretations. In epistemology, the attempt to eliminate cartasense subject/object paradigm, and also – the desire to transplant the methods of the Humanities on soil scientific disciplines, which creates an understanding of life and its phenomena as structures of the language.

Postmodern “challenge” classic rationality is to try to “flip” a well-established meanings with the aim of going beyond their limits, leading to a broader interpretation of rationality, which is understood not only as a method of understanding reality based on reason, but also as a structure that has its own laws and peculiarities. Postmodernism, preferring the “extensiveness of the surface” thoughts before the “intensity” of its “vertical” emphasizes “knowledge” as a methodological research tool “many”, which is the de facto multiplicity of interpretations. In epistemology, the attempt to eliminate cartasense subject/object paradigm, and also – the desire to transplant the methods of the Humanities on soil scientific disciplines, which creates an understanding of life and its phenomena as structures of the language.
Моравецький О. М. Особливості раціональності у дискурсі постмодернізму / О. М. Моравецький // Актуальні проблеми філософії та соціології: Науково-практичний журнал / Голов. ред. Д. В. Яковлев; відпов. секретар І. В. Шамша; Міністерство освіти і науки України; Національний університет "Одеська юридична академія". - Одеса, 2017. - Вип. 19. - С. 58-61.
Keywords: наука; наукове пізнання; раціональність; постмодернізм; дискурс; наука; научное познание; рациональность; постмодернизм; дискурс; science; scientific knowledge; rationality; postmodernism; discourse